2016
DOI: 10.1523/eneuro.0174-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Cocaine- and Amphetamine-Regulated Transcript in Vagal Afferents in the Mouse Are Unaltered in Response to Metabolic Challenges

Abstract: Visual Overview

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…(n = 3; unpaired two-tailed t-test p = 0.703) across a spectrum of physiological conditions. Furthermore, we replicate a contradictory report (Yuan et al, 2016) demonstrating that food availability had no impact on CART expression in the left NG during the light phase. We hypothesized that food intake may account for the apparent paradox and therefore quantified the amount of food consumed in either of these experimental feeding paradigms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…(n = 3; unpaired two-tailed t-test p = 0.703) across a spectrum of physiological conditions. Furthermore, we replicate a contradictory report (Yuan et al, 2016) demonstrating that food availability had no impact on CART expression in the left NG during the light phase. We hypothesized that food intake may account for the apparent paradox and therefore quantified the amount of food consumed in either of these experimental feeding paradigms.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, the site of action of NG CART and its role in the control of food intake remain controversial. A recent study failed to observe eating-induced CART expression changes in the NG during the light phase (Yuan et al, 2016). Although 3 rd and 4 th ventricular injection of exogenous CART reduced food intake (Aja et al, 2002;Skibicka et al, 2009;Zheng et al, 2002), intraparenchymal NTS (intraNTS) injection failed to reduce short-term sucrose intake (Zheng et al, 2002), or 24 h intake of chow (Skibicka et al, 2009), raising the question of whether NG CART release into the NTS is capable of affecting eating behavior.…”
Section: Introductionmentioning
confidence: 99%
“…S6D-G). Because these neuropeptides are known to be expressed both in the periphery(25)(26)(27)(28)(29) and CNS (24), we used a local viral delivery approach to target these neurons and avoid CNS effects. Injection of retrograde adeno-associated virus (AAVrg)-FLEX-tdTomato (30) revealed a prominent population of tdTomato+ neurons in the ileum, and colon myenteric plexus of Cartpt Cre(31) and Npy Cre (32) mice(Fig.…”
mentioning
confidence: 99%
“…This discrepancy could be related to different duration of fasting between experiments, even if our conditions (48-h fasting) were close to that of the earlier studies (24–48 h). A very recent study in mice also failed to reproduce this metabolic switch of VAN from an anorectic to orexigenic phenotype (44). Using confocal microscopy to visualize all afferent visceral C-fibers of the vagus nerve, these authors showed that the neuropeptide CART was not regulated by metabolic challenge (fasting or high-fat diet).…”
Section: Discussionmentioning
confidence: 99%